Integrated simulation of the production and financial performance of supply chain : the case of Vapo Oy Pellets - Rajala, Silja (2012)
Supply chain managers seek to find the most optimal solutions in business considering producing, delivering and warehousing. Simulation possibilities support supply chain decision making by enabling what-if-scenarios and supply chain performance measurement. This study introduces an integrated simulation of the production and financial performance of supply chain. Return on investment, ROI, is an indicator for measuring financial performance. Simulation model was developed for the case company of Vapo Oy Pellets. The study was conducted by design science research method, which enables combining theoretical base and practical problem solving in designing. The developed model consists of five functional parts: Master, Production, Procurement, Sales and Distribution. Simulation model allows user to input scenarios, which finally lead to supply chain ROI-%-calculation. ROIcalculation is based on operating profit (dividend) and capital invested in business operations (divisor). In order to calculate ROI-%, model both derives business related data from Sales and Operations Planning (S&OP) -models, and utilizes previous year's actuals.